Pregled temeljnih teoretskih problemov posebnega dela KZ-1 - Korošec, Damjan (Podjetje in delo, 2018)
Years ago, a group of criminal law professors from the Faculty of Law of the University of Ljubljana started a test project of a theoretically thorough commentary of the special part of the Slovenian Criminal Code (CC-1). This project grew into a year-long monumental research. We called it "Full Scientific Commentary of the Special Part of CC-1", because it delivers the most thorough analysis of legal theoretical questions of each and every Slovenian incrimination norm the Slovenian criminal legal science is capable of in given realities. The project is now finished and the text is in the form of several thousand pages to be published in the upcoming weeks. In this article, a summary of the overview of critical thoughts on the special part of the Slovenian CC-1 - as results of the research - is published for the first time. The special part of the Slovenian CC-1 is far from optimal. It is ridden with many systemic and other deficits. A lot of work will be needed to improve it, especially on the legislative level. The most severe deficits seem to be in the areas of the so-called collective crimes, in incriminations - where plural forms of substantives are used by the legislator - the objective prerequisite of punishability, and the praeterintentional result.
Keywords: hujša posledica; kazensko pravo; kolektivno kaznivo dejanje; KZ-1; objektivni pogoj kaznivosti; posebni del; Slovenija